(untitled) (IPS Journal of Toxicology, 2021)
Aim: To ascertain early detection of possible kidney injuries in albino rats exposed to formaldehyde by assessing cystatin C, serum electrolytes, urea and creatinine. Materials/Methods: Thirty healthy adult male albino rats, weighing between 100 to 120 grams were randomly divided into three groups A, B and C. Group A served as control. Group B was exposed to low dose (100ppm of Formaldehyde), 3 hrs per day for four weeks, while group C was exposed to high Dose-200ppm of formaldehyde 3 hrs per day for four weeks. At the end of the exposure period, the rats were sacrificed by decapitation under chloroform anesthesia, and 4 ml of blood samples was collected from each rat into a plain bottle. The whole blood was allowed to clot, retracted and centrifuged at 3000 rpm for 10 minutes and serum separated. The serum was stored at -20˚C until analyses for serum electrolytes, creatinine and cystatin C. Serum electrolytes were determined using Ion selective electrode, urea and creatinine were determined using spectrophotometric methods while cystatin C was analyzed using Eliza. Data obtained was analyzed using SPSS. Results: The concentrations of the serum electrolytes, sodium. Potassium, bicarbonate and chloride were compared across the three group, they were not statistically significant (p>0.05). Urea was significantly higher in group C when compared with low dose B and control group A (P<0.05). Also, when the low dose group B was compared with the high dose group C, it was statistically significant. Creatinine concentrations were significantly higher in group C when compared with the control group A, while group B was not significant when compared with group A. Finally, the cystatin C concentrations were also significant when groups B, C were compared with the control group. Conclusion: Formaldehyde exposures may induce a gradual deterioration of renal functions in chronically exposed albino rats. Serum electrolytes, urea and creatinine may not be sufficient to indicate an early sign of kidney damage. From the study, serum cystatin C may be a better marker of renal impairment in the early stages.